THE EFFECT OF PORTFOLIO SIZE ON THE FINANCIAL PERFORMANCE OF PORTFOLIOS OF INVESTMENT FIRMS IN KENYA - KIMANI, MBOGO PETER; ADUDA, DR. JOSIAH (International Journal of Finance and Accounting, 2016)
Purpose The purpose of this study was to determine the effect of portfolio size on the financial performance of portfolios of investment firms in Kenya. Methodology: The research design adopted a descriptive survey study. This implied that the total population of this study is 90 firms as given by the Kenya Association of Investment Groups (KAIG). For representativeness purposes, the current study took a sample size of 50% of the population. This was 45 firms. The study used secondary data from the financial statements of the investments firms. The selected period was 5 years. The researcher used frequencies, averages and percentages in this study. The researcher used Statistical Package for Social Sciences (SPSS) to generate the descriptive statistics and also to generate inferential results. Regression analysis was used to demonstrate the relationship between the portfolio size and the performance of investment firms. Results: The finding reveal that investments firms in Kenya had put the biggest allocation of funds in stocks, followed by real estate portfolio and the least holding was in bond and money market funds. The findings also reveal that that the stocks portfolio generated the highest returns followed by bond and money market returns while real estate portfolio generated the least returns. Unique contribution to theory, practice and policy: It was recommended that investment managers should consider increasing the number of stocks from the current average of 13 stocks to between 16 to 20 stocks. Such a portfolio size would be optimal since approximately 91% of risk would have been diversified. This will solve the question in mind of investment managers which has been as to how many individual stocks or investments are needed to compose an optimal portfolio. An optimal portfolio is preferred over a maximized portfolio due to the risk return tradeoff.